International Group Exhibitions - The Coffee: Another Distance - Antoniou, Klitsa (My University, 2026)
The Coffee: Another Distance The Municipality of Limassol and the Municipal Arts Centre - Papadakis Warehouses in collaboration with BPRarts Cultural Management Curated by Catherine Louis Nikita, Art Historian and Director of BPRarts Cultural Management and texts by Aspasia Papadima. Cyprus